Nonenzymatic synthesis of anomerically pure, mannosyl-based molecular probes for scramblase identification studies - Picca, Giovanni; Probst, Markus; Langenegger, Simon M.; Khorev, Oleg; Bütikofer, Peter; Menon, Anant K.; Häner, Robert (Beilstein Journal of Organic Chemistry, 2020)
The chemical synthesis of molecular probes to identify and study membrane proteins involved in the biological pathway of protein glycosylation is described. Two short-chain glycolipid analogs that mimic the naturally occurring substrate mannosyl phosphoryl dolichol exhibit either photoreactive and clickable properties or allow the use of a fluorescence readout. Both probes consist of a hydrophilic mannose headgroup that is linked to a citronellol derivative via a phosphodiester bridge. Moreover, a novel phosphoramidite chemistry-based method offers a straightforward approach for the non-enzymatic incorporation of the saccharide moiety in an anomerically pure form.
Keywords: carbohydrates; citronellol; phosphoramidite; photoclickable glycolipid analogs; scramblase